Soporte nutricional en el paciente crítico : una puesta al día (2008)
ABSTRACT: Patients in critical conditions present alterations in organs and metabolic systems that demand an appropriate medical and nutritional support which is fundamental to prevent further deterioration and to improve clinical outcomes. The objective of this review is to bring up to date the current information and publications from scientific databases about the advances in nutritional therapies for critical ill patients; this review is important to conclude that specialized nutritional support can benefit critical ill patients even more when this is implemented opportunely with appropriate technical conditions by professionals. In order to avoid risk of severe complications for these patients, professionals in nutrition must be part of the clinical team giving integral attention to critical ill patients.